1983
DOI: 10.1080/00207598308247480
|View full text |Cite
|
Sign up to set email alerts
|

Level of Processing Effects on Hemispheric Asymmetries With Kana (Japanese Phonetic Symbols) Words

Abstract: Two experiments were conducted to examine the role of levels and types of higher‐order processing to which the stimulus was subjected. In the experiment 1, two different physical identity matches with Kana (Japanese phonetic symbols) words, one involving two operations while the other involves one operation, were required, and no visual field difference was found though two operations task yielded longer RTs than in one operation task. Experiment 2, where two different name identity matches, one involving ling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1985
1985
2003
2003

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…In contrast to CVC stimuli in English, a three-character kana string need not be encoded as a single unit because it is pronounced exactly as it is spelled, character by character. Although there was a robust RVF-LH advantage for identifying these kana stimuli in Japanese speakers (see also Hatta, 1983; Ohtani, 1984), there were no hemispheric differences in QE scores. Instead, the QE scores were equally high on LVF-RH, RVF-LH, and redundant bilateral trials, consistent with sequential processing of the individual letters and with the results for nonletter symbols reported in the present experiment.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to CVC stimuli in English, a three-character kana string need not be encoded as a single unit because it is pronounced exactly as it is spelled, character by character. Although there was a robust RVF-LH advantage for identifying these kana stimuli in Japanese speakers (see also Hatta, 1983; Ohtani, 1984), there were no hemispheric differences in QE scores. Instead, the QE scores were equally high on LVF-RH, RVF-LH, and redundant bilateral trials, consistent with sequential processing of the individual letters and with the results for nonletter symbols reported in the present experiment.…”
Section: Resultsmentioning
confidence: 99%
“…Hatta postulated two types of visual tasks which involve different levels of information processing, one referred to as a simple recognition task and the other referred to as a higher-order processing task. Hatta (1982Hatta ( , 1983b hypothesized that there are two types of higher-order information processing, one relying more on the linguistic code (L-type) and the other relying on the nonlinguistic (imagery) code (I-type). The former calls for stronger engagement of the left hemisphere while the latter calls for a greater contribution from the right hemisphere.…”
Section: Discussionmentioning
confidence: 99%
“…The Mixed condition seemed to require a much deeper level of processing compared to the Kanji and the Arabic conditions. A number of the previous research has clarified the effect of levels of processing on hemispheric asymmetry (e.g., Bryden & Allard, 1976;Cohen, 1983;Hatta, 1983;Moscovitch, 1979Moscovitch, , 1986. In addition, a number of research have reported that a right hemisphere more involved in recognizing Kanji characters (e.g., Endo, Shimizu, & Nakamura, 1981;Hatta, 1977Hatta, , 1978Hatta, Katoh, & Aitani, 1983;Sasanuma, Itoh, Mori, & Kobayashi, 1977), compared to that for recognizing other scripts (e.g., alphabets, Arabic numerals and Kanas).…”
mentioning
confidence: 99%